Uso do metabissulfito de sódio na pós-colheita do camarão marinho Litopenaeus vannamei (Boone,1931) - GÓES, Lílian Maria Nery de Barros (2005)
In global aquaculture, shrimp farming has stood out as a highly profitable activity, contributing to the economic growth of agribusiness. In Brazil, the activity performs well, mobilizing large investments and generating jobs mainly in the Northeast, whose production is largely destined for exports. In this context, the quality of the product assumes fundamental importance, being necessary the use of additives. Sodium metabisulfite is the most widely used preservative in shrimp farming, acting as a molecular oxygen inhibiting agent, preventing the melanose reaction. In this way, the objective was to contribute to the reduction of the residual content of this preservative in cultivated prawns destined to the external and internal market. Shrimp of the Litopenaeus vannamei classification 81/100 were submitted to ten concentrations of sodium metabisulphite (from 1 to 10%) during five exposure times (10, 15, 20, 25 and 30 min) in order to establish the relationship Between the preservative concentration and the immersion time of the shrimp. The different methods of measuring SO2 concentration in shrimps and the residual levels of SO2 in frozen shrimps were also evaluated during the 1-month period. The results were statistically analyzed using multiple linear models. Concentrations of metabisulfite, above 4%, exceeded the maximum limits permitted by current legislation for cold and frozen shrimp (100 ppm residual SO2) being inappropriate for practical use. The shrimp submitted to concentration 1% showed good conservation during the first 20 days, however after this period the onset of melanose was detected. Concentrations 2 and 3% adequately preserved the product for a period of 30 days, with satisfactory SO2 levels. Storage time did not significantly influence (P <0.05) sulfite levels. The adapted Adolfo Lutz titration method presented great sensitivity for the detection of free and combined sulphites, not the same with the methods of cold titration and the reactive tape, in order of sensitivity for free sulfites. The antimicrobial action was directly proportional to the preservative concentration. It is concluded that the concentrations of sodium metabisulphite currently used in practice are excessively high, leading to wastage of preservative and capital in production and generating high levels of SO2 in shrimp